Oculomotor and Vestibular Findings in Gaucher Disease Type 3 and Their Correlation with Neurological Findings - Bremova-Ertl, Tatiana; Schiffmann, Raphael; Patterson, Marc C.; Belmatoug, Nadia; Billette de Villemeur, Thierry; Bardins, Stanislavs; Frenzel, Claudia; Malinová, Věra; Naumann, Silvia; Arndt, Juliane; Mengel, Eugen; Reinke, Jörg; et al. (Frontiers in Neurology, 2018)
Objectives: To evaluate the function of the oculomotor and vestibular systems and to correlate these findings with the clinical status in patients with Gaucher disease type 3 (GD3). The goal of this cross-sectional and longitudinal study was to find oculomotor biomarkers for future clinical trials. Methods: Twenty-six patients with GD3 were assessed for eligibility and 21 were able to perform at least one task. Horizontal and vertical reflexive saccades, smooth pursuit, gaze-holding, optokinetic nystagmus and horizontal vestibulo-ocular reflex (VOR) were examined by video-oculography/video-head impulse test and compared concurrently with 33 healthy controls. The Scale for the Assessment and Rating of Ataxia (SARA), the modified Severity Scoring Tool (mSST) and Grooved Pegboard Test (GPT) were administered to assess overall neurological function. Eleven patients were also re-assessed after one year. Results: Nine out of 17 patients exhibited gaze-holding deficits. One patient had upbeat nystagmus. Three patients presented with bilateral abducens palsy in combination with central oculomotor disorders, suggesting a bilateral involvement of the abducens nucleus. Horizontal angular VOR gain was reduced in all patients (0.66 ± 0.37) compared with controls (1.1 ± 0.11, p < 0.001). Most strongly correlated with clinical rating scales were peak velocity of downward saccades (SARA: ρ = -0.752, p < 0.0005; mSST: ρ = -0.611, p = 0.003; GPT: ρ = -0.649, p = 0.005) and duration of vertical saccades (SARA: ρ = 0.806, p < 0.001; mSST: ρ = 0.700, p < 0.0005; GPT: ρ = 0.558, p = 0.02) together with the VOR gain (SARA: ρ = -0.63, p =0.016; mSST: ρ = -0.725, p = 0.003; GPT: ρ = -0.666, p = 0.004). Vertical smooth pursuit gain decreased significantly at follow-up. Interpretation: This study shows neuronal degeneration of the brainstem and cerebellum with combined involvement of both supranuclear and nuclear oculomotor structures and the vestibular system in GD3. We also identified oculomotor parameters that correlate with the neurological status and can be used as biomarkers in future clinical trials.